The epistemics of populism and the politics of uncertainty - Richard Bronk; Wade Jacoby (London School of Economics and Political Science (LSE), European Institute, 2020)
This paper discusses epistemic aspects of populism – especially its link with radical uncertainty and the tribal construction of facts – that have so far received relatively little attention. We argue that populism is less a backward-looking phenomenon feeding off existing grievances than a narrative-based reaction to an increasingly unsettled future. Many economic factors isolated as causes of populism – especially rapid technological innovation, deregulation, and the globalisation of networks – entail a high degree of indeterminacy in social systems; and the corresponding uncertainty facing voters is a catalyst for many of the pathologies of populism isolated in the literature. In particular, uncertainty undermines the credibility of experts, while the disorientation and anxiety it induces increase reliance on simple narratives to structure expectations. The paper explores the role of narrative entrepreneurs, the relationship between narratives and power, and the dynamics of narrative coups designed to create alternative facts and perform a new reality.
Keywords: 330; Uncertainty; narrative coups; tribal construction of facts; distrust of experts; populist turn